Practice of Remote Teaching and the Student with Disabilities in the Pandemic of Covid-19: The Undeniable Right to Access to Education (Global Journal of Human-Social Science, 2023)
The right to education is a fundamental and common guarantee for all and should not be violated due to the ineptitude of schools in assisting students with disabilities who need to get to know their students and have a good interaction with their families so that together can develop the best teaching strategies during the state of calamity such as the period of the Sars-Cov- 2 pandemic Thus the research aims to analyze the difficulties that students with disabilities physical visual auditory and intellectual encountered in the practice of remote teaching during the pandemic period in addition to discussing the protection of Inclusive Education in crisis scenarios making an interface with the legislation to demonstrate the importance that the laws have to ensure the right to Education and the permanence of the student in school The methodology adopted consisted of using the most celebrated research sources such as doctrine legislation academic platforms and computerized benefits After analyzing the results it was observed that there was no adequate planning by the schools for the adoption of remote teaching especially with regard to the public of people with disabilities
Keywords: remote learning; right to education; covid- 19 pandemic; student with disabilities